Reverse Szabo technique for stenting a single major aorto-pulmonary collateral vessel in pulmonary atresia with ventricular septal defect - Polivenok, Igor V. (Transl Pediatr, 2016)
Management of pulmonary atresia with ventricular septal defect (PA-VSD) in the neonatal period presents numerous challenges. Endovascular stenting of the ductus arteriosus or of a collateral vessel in ductal-dependent pulmonary circulation as an alternative to the Blalock-Taussig (BT) shunt has become increasingly popular in the last decades. The utilization of the reverse Szabo (anchor-wire) technique for single collateral vessel stenting in a case of PA-VSD is described.